Until the Dawn - Camden, Elizabeth 1948- (Minneapolis, Minnesota : Bethany House, a division of Baker Publishing Group, 2015)
"In 1898, an abandoned mansion overlooking the Hudson River Valley proves a refuge and resource for Sophie van Riijn in her volunteer work for the Weather Bureau until Quentin Vandermark, a long-lost heir of the estate, shows up"--
Keywords: Family secrets -- Fiction; Man-woman relationships -- Fiction; Hudson River Valley (N.Y. and N.J.) -- Fiction -- Social life and customs -- 19th century; Historical fiction; Christian fiction; Romance fiction